Visual performance after interface haemorrhage during laser in situ keratomileusis. Issue 6 (1st June 2003) - Vajpayee, R B; Balasubramanya, R; Rani, A; Sharma, N; Titiyal, J S; Pandey, R M
Abstract : Aim: To study the visual performance in eyes with interface haemorrhage during laser assisted in situ keratomileusis (LASIK). Methods: Case records of 20 patients, who had bleeding from the limbal vessels in one eye during LASIK (group 1) and uncomplicated surgery in the fellow eye (group 2) were studied. The parameters evaluated were uncorrected visual acuity (UCVA) best corrected visual acuity (BCVA), spherical equivalent of refraction (SEQ), contrast sensitivity, and glare acuity preoperatively and at 1, 3, and 6 months postoperatively. Results: The mean preoperative SEQ in group 1 and 2 eyes was −5.79 (2.3) D and −5.27 (1.68) D, respectively. The mean decimal UCVA at 6 months after LASIK in group 1 and 2 eyes were 0.6 (0.2) and 1.0 respectively (p<0.001). The mean decimal BCVA at 1 week after LASIK in group 1 and 2 eyes were 0.89 (0.04) and 1.0 respectively (p<0.05). However, all eyes had a BCVA of 6/6 at 1, 3, and 6 months after LASIK. The mean contrast sensitivity values preoperatively in group 1 and 2 eyes were 161.3 (8.7) and 172 (68.2) respectively. There was a significant decrease in group 1 at 6 months (102 (60.5) (p<0.01)) compared to group 2. The decimal glare acuity preoperatively in group 1 and 2 eyes was 0.95 (0.11) and 0.89 (0.12), respectively. It decreased significantly in group 1 (0.7) (0.1 (p<0.01)) compared to group 2 at the 6 month follow up. Conclusion: Occurrence of intraoperative interface haemorrhage may affect the visual performance following LASIK surgery.